Models of environmental awareness: exploring their nature and role in environmental education – a systematic review - Harlys Rivas Perea; Andrés Rey Piedrahita; Óscar Eugenio Tamayo Alzate (Heliyon, 2025)
The increasing global concern over environmental degradation has prompted the development of conceptual models to enhance environmental awareness, particularly within educational contexts aimed at fostering sustainability. This systematic review synthesises research on environmental awareness models, exploring their definitions, conceptualisations, and roles in environmental education across diverse settings. Utilising the PRISMA framework, a comprehensive search was conducted in leading databases, namely SCOPUS, Web of Science, Springer, and Wiley Online Core Collection, yielding a total of 6,444 peer-reviewed articles from 2018 to 2024. This extensive review process identified 20 studies that were subjected to in-depth analysis. The review findings signify noteworthy theoretical advancements, with models integrating cognitive, emotional, and situational dimensions to devise innovative assessment tools and targeted educational strategies that promote sustainable behaviours. However, persistent challenges remain, including inadequate sampling techniques, limited use of advanced technologies such as big data and AI, and insufficient interdisciplinary collaboration, all of which hinder broader application. The findings emphasise the critical role of both formal and informal education in cultivating environmental awareness, highlighting how these frameworks shape sustainability-oriented attitudes and actions. The study also underscores gaps, such as the need for culturally sensitive models and longitudinal evaluations, and proposes comprehensive, technology-enhanced, and interdisciplinary approaches to address them. By elucidating the interplay between environmental awareness, education, and sustainability, this review offers actionable insights for future research and the design of impactful educational interventions, advocating for strategies that bridge theoretical innovation with practical implementation to foster a generation of environmentally responsible citizens committed to sustainable futures.